2013
DOI: 10.3892/mco.2013.112
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the outcome between cervical adenocarcinoma and squamous cell carcinoma patients with adjuvant radiotherapy following radical surgery: SGSG/TGCU Intergroup Surveillance

Abstract: The efficacy of radiotherapy (RT) for adenocarcinoma (AC) is controversial, although patients with AC of the uterine cervix are treated in a similar manner to those with squamous cell carcinoma (SCC). This retrospective study was conducted to evaluate the efficacy of adjuvant RT for patients with AC compared to those with SCC following radical hysterectomy. A total of 820 patients with stage IB-IIB cervical cancer, who underwent type III radical hysterectomy between 1997 and 2003, were retrospectively examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 21 publications
4
29
2
Order By: Relevance
“…Therefore, survival may be similar in early-stage cervical SCC and AC after radical surgery. Several studies confirm our hypothesis, showing that there are no significant differences in survival between early-stage cervical SCC and AC after radical hysterectomy with lymphadenectomy [ 4 23 27 30 31 32 ]. Our findings support the hypothesis that patients with cervical AC have distinct clinical outcomes from patients with cervical SCC following the different treatment strategies.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Therefore, survival may be similar in early-stage cervical SCC and AC after radical surgery. Several studies confirm our hypothesis, showing that there are no significant differences in survival between early-stage cervical SCC and AC after radical hysterectomy with lymphadenectomy [ 4 23 27 30 31 32 ]. Our findings support the hypothesis that patients with cervical AC have distinct clinical outcomes from patients with cervical SCC following the different treatment strategies.…”
Section: Discussionsupporting
confidence: 72%
“…However, the study did not perform subgroup analysis of the effect of local treatment on survival. Several studies including ours have found that in patients who received definitive radiotherapy or adjuvant radiotherapy (high-risk factors), AC subtype was associated with worse survival compared with SCC subtype, whereas histologic subtype did not affect the survival outcome of patients with low-risk group after radical hysterectomy [ 19 25 26 27 28 29 ]. Therefore, cervical AC may be resistant to radiotherapy, and surgical treatment may be the optimal treatment for early-stage cervical AC.…”
Section: Discussionmentioning
confidence: 99%
“…Given the relatively small sample size used in this pilot study, it would be premature to draw any conclusion from this negative finding; however, it is possible that ultimately other imaging markers may be superior to texture features for prediction of the histological type (such as perfusion parameters obtained by dynamic contrast-enhanced MRI ( 7 ) or intravoxel incoherent motion imaging ( 22 )). Although the dominant factors for patient management are FIGO-stage, histological differentiation and nodal status, the histological subtype is also an independent predictor for outcome and treatment response ( 23 ). Furthermore, there was no significant correlation with the FIGO stage.…”
Section: Discussionmentioning
confidence: 99%
“…Some retrospective studies revealed poorer overall survival (OS) than that of SCC ( Table 1 ). To improve the OS in CCRT some trials that concomitant agent changed with platinum and paclitaxl,or the subsequent CT with full dose paclitaxel and carboplatin ( 1 , 2 ).…”
Section: Introductionmentioning
confidence: 99%